The Legal Importance of Registering Intellectual Property for Creative Economy Stakeholder as Loan Collateral - Sri Handayani; Muhammad Rasyid; Saut Parulian Panjaitan (Simbur Cahaya, 2024)
Intellectual Property as the foundation of the creative economy can provide massive economic benefits with the intellectual capacity of the nation, the design and development of intellectual property-based financing schemes. however, the utilization of intellectual property resulting from the creativity of creative economy practitioners in the application of intellectual property-based financing schemes must have record or certificate of intellectual property. The awareness of creative economy practitioner in Indonesia is currently low when it comes to registering intellectual property products. This research is a normative legal study based on primary legal sources consisting of legislative regulation. It is further supported by secondary data obtained through literature reviews and an analysis of various related literature regarding the core issue of this study. Registration and recording of intellectual property in Indonesia remain low because the public, especially creative economy practitioners have limited knowledge about the intricacies of registration and recording. Additionally, the public perceives registering and recording as futile due to the weak enforcement of intellectual property laws. Creative economy practitioners also lack awareness of the benefits of registration or recording as a requirement for obtaining capital through intellectual property-based financing schemes. Efforts made by the government include improving the enforcement of intellectual property laws and simplifying and reducing the cost of intellectual property registration and recording. The support of the intellectual property recording mechanism as collateral for loans can assist creative economy practitioners in obtaining funding.